2008
DOI: 10.1111/j.1600-0854.2008.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of TMV Movement Protein Particles Associated with the Targeting of RNA to Plasmodesmata

Abstract: The cell-to-cell movement of Tobacco mosaic virus through plasmodesmata (PD) requires virus-encoded movement protein (MP). The MP targets PD through the endoplasmic reticulum (ER)/actin network, whereas the intercellular movement of the viral RNA genome has been correlated with the association of the MP with mobile, microtubule-proximal particles in cells at the leading front of infection as well as the accumulation of the protein on the microtubule network during later infection stages. To understand how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 88 publications
(170 reference statements)
3
119
0
4
Order By: Relevance
“…Since MP traffics in the ER membrane (Brill et al, 2000;Wright et al, 2007;GuenouneGelbart et al, 2008;Sambade et al, 2008), this finding is in agreement with the reported ability of ER membrane proteins to continue their trafficking in the membrane upon disruption of actin filaments with LatB (Runions et al, 2006). Nevertheless, although an effect of LatB treatment on the spread of infection was not observed, the absence of intact actin filaments has important effects with respect to the efficiency of PD targeting.…”
Section: Tmv Movement Is Independent Of Actinsupporting
confidence: 79%
See 2 more Smart Citations
“…Since MP traffics in the ER membrane (Brill et al, 2000;Wright et al, 2007;GuenouneGelbart et al, 2008;Sambade et al, 2008), this finding is in agreement with the reported ability of ER membrane proteins to continue their trafficking in the membrane upon disruption of actin filaments with LatB (Runions et al, 2006). Nevertheless, although an effect of LatB treatment on the spread of infection was not observed, the absence of intact actin filaments has important effects with respect to the efficiency of PD targeting.…”
Section: Tmv Movement Is Independent Of Actinsupporting
confidence: 79%
“…The inhibition of Golgi trafficking upon transient ABD2:GFP expression may thus reflect inhibition of the trafficking of protein complexes in the ER membrane. Given that TMV movement occurs via diffusion in the ER membrane (Brill et al, 2000;Wright et al, 2007;Guenoune-Gelbart et al, 2008;Sambade et al, 2008), we propose that the ABD2:GFP-mediated restriction in TMV movement occurs through obstruction of the ER membrane by immobilized protein complexes (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of infection, as well as when ectopically expressed, the MP associates with PD, the ER/actin network, and microtubules (Heinlein et al, 1995Reichel and Beachy, 1998;Wright et al, 2007;Sambade et al, 2008;Hofmann et al, 2009;Boutant et al, 2010;Peña and Heinlein, 2012;Supplemental Fig. S1).…”
mentioning
confidence: 99%
“…Este proceso parece requerir la interacción de la MP con elementos del citoesqueleto intacto o con componentes individuales de los MT o los MF [Ashby et al, 2006;Wright et al, 2007;Sambade et al, 2008;Hofmann et al, 2009]. En este sentido, se ha especulado que los motivos homólogos a la tubulina vegetal presentes en p30 ( Fig.…”
Section: Superfamilia "30k"unclassified